Local Content Curriculum Management at MA Al Asyhar Bungah Gresik - Haris, Muhammad (Mudir : Jurnal Manajemen Pendidikan, 2023)
Abstract: The local content curriculum aims to equip students with the knowledge, skills, and attitudes necessary to understand society and the environment in accordance with local values and to maintain regional and national development. As a result, real efforts are required to include local content in the curriculum, including the study of the yellow book, in order to strengthen the role that local content plays in preserving cultural values in society. The age of globalization has advanced and modernized education and is still developing modern learning. However, educational establishments like MA Al Asyhar Bungah Gresik also preserve the legacy of previous scholars by studying the yellow book. This instructive establishment conveys the learning of the yellow book into the learning material being examined. The Yellow Book are books composed by past researchers which contain examples about Islam, be it in the field of fiqh, aqidah or others, which are composed utilizing Arabic letters. The presence of yellow books is to assist with making it more straightforward for individuals to grasp Islam through the work or compositions of a researcher.